On Marxism, Pragmatism and Critical Urban Studies. (12th September 2013) - Bridge, Gary
Abstract This article explores the possibilities of philosophical pragmatism for critical theory in urban studies. It points to the philosophical connections between pragmatism and the mainstay of critical theory in urban studies — Marxism. The article suggests how these philosophical roots as well as contemporary developments of pragmatism in social science (and in critical theory) open out the terrain of critical urban studies to make it more pluralist and democratic, theoretically and politically. The article concludes by looking at some of the consequences of this pragmatic turn for critical urban theory.